Polymeric Chitosan Gel Modulates Inflammatory Responses to Prevent Peritoneal Adhesion in Rats - Makarim, Fadhli Rizal; Ekasaputra, Vito Mahendra; Arnandha, Defan Adlill; Sahardin, Renaldy; Khayin, Iqbal Yusuf (International Journal of Cell and Biomedical Science, 2022)
Peritoneal adhesions are a pathological response to injury that connects adjacent structures that cause by inflammatory response such as IL-1 and IL-6. The current strategies to minimize or prevent peritoneal adhesions are very limited. Chitosan was found have antiinflammatory effect. However, chitosan hydropphobic properties give poor solubility in physiological solvent such as peritoneal fluid. Our study aims to investigate the effect of polymeric chitosan gel in the prevention of peritoneal adhesion through modulating IL-1 and IL-6 after laparotomy. Ten rats were divided into a control group and treated group. Laparotomy model was done with proper procedure. Illeum were scratch using cytobrush to mimic peritoneal adhesions. In the treated group, the defect was covered with Mediclore®. After 14 days, IL-1 and IL-6 were analyzed using ELISA from peritoneal fluid serum and macroscopic observation of adhesion were made. All animals in control group showed high grade of adhesin while treated group showed a filmy peritoneal adhesion. Group treated with Mediclore® showed a lower IL-1 levels compared to control group. Treated group showed a better control at inflammation by scoring lower IL-6 levels compared to control group. In conclusion, polymeric chitosan gel prevents peritoneal adhesions through modulation of inflammatory cytokines after laparotomy in rats. Keywords: chitosan, IL-1, IL-6, peritoneal adhesions, laparotomy